Impact of Influenza Vaccination on Mortality in the Oldest Old: A Propensity Score-Matched Cohort Study - Pauline Walzer (Vaccines, 2020)
Influenza remains a major cause of illness and death in geriatric populations. While the influenza vaccine has successfully reduced morbidity and mortality, its effectiveness is suspected to decrease with age. The aim of this study was to assess the impact of influenza vaccination on all-cause mortality in very old ambulatory subjects. We conducted a prospective cohort study from 1 July 2016 to 31 June 2017 in a large unselected ambulatory population aged over 80 years. We compared all-cause mortality in vaccinated versus unvaccinated subjects after propensity-score matching, to control for age, sex and comorbidities. Among the 9149 patients included, with mean age 86 years, 4380 (47.9%) were vaccinated against influenza. In total, 5253 (57.4%) had at least one chronic disease. The most commonly vaccinated patients were those with chronic respiratory failure (76.3%) and the least commonly vaccinated were those suffering from Parkinson’s disease (28.5%). Overall, 2084 patients (22.8%) died during the study. After propensity score matching, the mortality was evaluated at 20.9% in the vaccinated group and 23.9% in the unvaccinated group (OR = 0.84 [0.75–0.93], p = 0.001). This decrease in mortality in the vaccinated group persisted whatever the age and Charlson Comorbidity index. In conclusion, nearly a half of this ambulatory elderly population received Influenza vaccine. After adjustment on comorbidities, influenza vaccination was associated with a significant decrease in all-cause mortality, even in the eldest multimorbid population. Improving immunization coverage in this frail older population is urgently needed.